Reduction of differential equations to algebraic ones - Boyko, V.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
In terms of singular reduction modules, i. e. singular modules of a nonclassical (conditional) symmetry, the question of reduction of differential equations to algebraic ones is studied.